2019
DOI: 10.3390/su11102864
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Tourism as a Sustainable Direction in Destination Development: An Empirical Examination of Visitor Behaviors

Abstract: Community-based tourism is an emerging form of sustainable tourism. Community-based tourism often brings various financial/non-financial benefits to local communities and maximizes sustainability at the local level. The present study was designed to uncover the role of community-based tourism performance in elucidating travelers’ post-purchase decision-making process for sustainable destination products by considering the moderating effect of sense of belonging. A quantitative approach was adopted for the achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 45 publications
(93 reference statements)
0
26
0
8
Order By: Relevance
“…Sustainable tourism is one of the most important topics in the global industry of tourism, sustainability being often seen as the reason for the competition developed between different tourist destinations [13]. Although tourists are showing more and more interest in sustainable and innovative proposals, the activities in the tourism industry are becoming less and less sustainable, many companies being in a situation where they do not have a clear innovative strategy, much less a strategy for sustainable growth and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable tourism is one of the most important topics in the global industry of tourism, sustainability being often seen as the reason for the competition developed between different tourist destinations [13]. Although tourists are showing more and more interest in sustainable and innovative proposals, the activities in the tourism industry are becoming less and less sustainable, many companies being in a situation where they do not have a clear innovative strategy, much less a strategy for sustainable growth and innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that the social context represented by SB has a significant positive impact on RI. Han et al [2019] in their research on community-based tourism came to a similar conclusion. Although a broader context of the sense of belonging was analyzed, of which SB is one aspect, it was observed that higher levels of this category correspond with a greater willingness to make recommendations.…”
Section: Conclusion and Limitations Of The Studymentioning
confidence: 63%
“…The Maramures region's representative elements for agritourism are numerous traditions, numerous rural resources (see Figure 9), some known on international level, and moreover well-preserved gastronomic elements-these aspects being highlighted from the responses of interviewed owners of agritourism structures. Recently, the return to nature and natural products or to the rural environment is becoming more pronounced; therefore the tourist focuses on the most natural food and wants an active involvement in the life of the community, as was highlighted by numerous studies [25,39,40]. The owners of agritourism structures from the regions under study (see Table 9 and Figure 10a,b) are aware of this aspect, as was proven by the survey.…”
mentioning
confidence: 83%